IDENTITY INSTRUMENTALIZATION AND PANCASILA DEMOCRACY IN ACEH, WEST KALIMANTAN, NORTH MALUKU - Razuni, Ganjar; Setia Budi, Rahardian Putra (Sosiohumaniora, 2026)
This article examines how identity was instrumentalized in local democratization through regional head elections in Aceh, West Kalimantan, and North Maluku during the 2017/2018 and 2024 electoral cycles, and how this process affected the substantive practice of Pancasila Democracy at the local level. Rather than treating identity politics itself as inherently polarizing, the article distinguishes between identity as a social fact, identity mobilization as the activation of group boundaries, and identity instrumentalization as the strategic use of ethnic, religious, and regional markers by political actors for electoral advantage. Using a qualitative comparative multiple-case design, the study analyzes institutional documents, election-related media archives, and peer-reviewed literature through qualitative content analysis and thematic comparison. The findings show three different patterns. In Aceh, Islamic identity and conflict memory were consolidated through local parties, former combatant networks, and clerical authority. In West Kalimantan, ethno-religious polarization in 2018 shifted toward cross-ethnic compromise in 2024, although primordial voting blocs remained politically relevant. In North Maluku, identity was mobilized situationally: elite resistance to a minority candidacy intensified religious appeals, yet many voters supported a more pluralist electoral outcome. The article argues that the instrumentalization of identity, rather than identity politics per se, weakens deliberation, inclusion, and civic equality, thereby reducing Pancasila to a normative symbol rather than an operational ethic of local democracy.